PERAN GURU PAI DALAM MENGINTERNALISASIKAN AKHLAK ISLAMI DI TENGAH BUDAYA DIGITAL PADA SISWA - Arifin; Khusnul Hamdani, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital culture has brought significant changes to patterns of interaction, ways of thinking, and the formation of students’ character, particularly at the Vocational High School (SMK) level. On one hand, digitalization provides easier access to information; on the other hand, it presents challenges such as moral degradation, low digital literacy, and increased exposure to negative content. This study aims to analyze the roles and strategies of Islamic Religious Education (PAI) teachers in internalizing Islamic morals amid digital culture, identify supporting and inhibiting factors, and examine students’ behavioral manifestations as outcomes of this internalization process. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that PAI teachers act as agents of digital moral transformation through strategies such as role modeling, habituation, integration of values in contextual learning, and strengthening Islamic digital literacy. Supporting factors include a religious school culture and institutional policy support, while inhibiting factors involve students’ low digital literacy, limited digital competence among teachers, and external environmental influences. The internalization of Islamic morals is reflected in the increasing awareness of students’ digital ethics, although it remains partial and gradual. This study underscores the importance of integrating moral education with digital literacy as an adaptive approach to addressing educational challenges in the digital era.